Resilience and Psychological Distress in Early Adulthood with Non-Suicidal Self-Injury: A Scoping Review - Atikah Amalia; Rismiyati E. Koesma; Roswiyani Roswiyani (Journal La Sociale, 2024)
According to Orenstein & Lewis (2021), young adults are at a transitional age and have demands on developmental tasks. When these demands are not met, it can cause feelings of suffering, activities that become obstacles and characterized by symptoms of anxiety and depression or called psychological disorders (Kalia & Knauft, 2020; Dharma et al, 2020). Psychological distress that are not balanced with adaptive problem solving can cause maladaptive distress, it called non-suicidal self-injury (Rahmasari, 2021). According to Hans et al (2022) bounce back is needed in young adults, so they can face the problem, or it called resilience. In the previous study by Khan & Ungar (2021), there were limited matters such as the search for coping strategies carried out by the sample in the study and protective factors from the emergence of self-harm and the non-specific definition of NSSI. Aims:identification research on resilience and psychological distress in young adults with NSSI. Method:scoping review. Result: 10 journals that met the inclusion criteria were selected. Hypothesis of this study is the results of the study indicate that the conditions of psychological distress in young adults with NSSI have low resilience and high levels of psychological distress. The benefits of this research theoretically are to enrich scientific references in the field of clinical psychology, especially regarding resilience and psychological disorders in young adults with NSSI and practically this research can be continued by taking into account several limitations and can be developed into interventions for young adults with NSSI.